Peran KH. Idham Chalid dalam Konferensi Islam Asia Afrika di Kota Bandung Tahun 1965 - Nurjaman, Andri; Sulaiman, Asep; Purnama, Agung (Historia Madania: Jurnal Ilmu Sejarah, 2020)
This article discusses the history and the role of KH Idham Chalid in organizing the Asian-African Islamic Conference in Bandung in 1965. The conference was held on 6-14 March 1965 in the city of Bandung precisely in Gedung Merdeka aimed at combating Â¬neo-colonialism and uniting the solidarity of Muslims of Asian and African nations. According to Sukarno, the conference was that every country in Asia and Africa could be free from all forms of colonialism and therefore the religion of Islam could flourish in every country. This Islamic Conference deals with how to contribute to the the greatness of Islam, to get complete independence and to organize solidarity. KH Idham Chalid became the central figure of the Asia Africa Islamic Conference. The method used in this study is the historical research method, while the steps of the research are as follows: First heuristic second critique third interpretation and fourth historiography. From this study, we have seen that KH Idham Chalid had given huge contribution to organize this important Islamic Conference and also could manage the potential conflict and debate among the delegation of Muslim countries.